Stereotactic Ablative Radiation Therapy for Large (≥5 cm) Non-small Cell Lung Carcinoma. Issue 5 (May 2021) - McDermott, R.L.; Mihai, A.; Dunne, M.; Keys, M.; O'Sullivan, S.; Thirion, P.; ElBeltagi, N.; Armstrong, J.G.
Abstract: Aims: Stereotactic ablative radiation therapy (SABR) is a standard of care for medically inoperable early stage non-small cell lung carcinoma. Tumours greater than 5 cm have been excluded from randomised trials using SABR and, hence, it is not used as a standard for larger lung tumours. However, improvements in radiation therapy techniques and the success of SABR in treatment of early stage disease may allow safe delivery of ablative doses to larger tumours. We analysed our experience with tumours ≥5 cm to determine the efficacy and toxicity profile of SABR in this setting. Materials and methods: We evaluated survival, control rates, patterns of failure and toxicity in patients with a tumour diameter larger than 5 cm that had no nodal or distant metastases treated with SABR technology. Patients had been treated in two centres since 2009 and were retrospectively analysed. All patients had positron emission tomography staging, were discussed at a tumour board and were documented to have no nodal or distant metastatic disease. Treatment outcomes were analysed using Kaplan–Meier estimates and compared using the Log-rank test. Cox regression was used to investigate the association between the survival outcomes and predictor variables. Results: In total, 86 patients were identified. Six patients had no follow-up imaging. Therefore, 80 patients were available for analysis. All patients were reclassified according to the updated AJCC eighth edition. The median follow-up was 19.6 months. No patients received neoadjuvant or concurrent systemic therapy. One patient received adjuvant systemic therapy. The median age at treatment was 77 years (range 58–91). Eighty-four per cent were stage T3N0M0 and 16% were staged T4N0M0. The median tumour diameter was 5.8 cm (range 5.0–9.3 cm). The median gross tumour volume, measured on a single phase of the respiratory cycle, was 45.7 cm 3 (range 12.1–203.3 cm 3 ). The median overall survival was 20.9 months (95% confidence interval 12.6–29.1 months). One-, 2- and 3-year overall survival was 71%, 48% and 32%, respectively. The median local failure-free survival was 19.5 months (95% confidence interval 14.4–24.6). The median disease-free survival was 15.1 months (95% confidence interval 9.9–20.4 months). Local control at 1, 2 and 3 years was 85% (95% confidence interval 76–94%), 71% (95% confidence interval 58–84%) and 57% (95% confidence interval 40–74%), respectively. Forty-four patients (55%) had any treatment failure (local, mediastinal, intrapulmonary or distant metastases). Out-of-field intrapulmonary disease progression was the most common mode of failure, occurring in 21 patients (26%). Local failure occurred in 19 patients (24%) – alone or in combination with other progression. Distant metastases occurred in 20 patients (25%). Neither histological subtype, tumour size nor gross tumour volume had a statistically significant effect on local failure-free survival. Two patients experienced grade 3 late dyspnoea. There were no other reported grade 3 or higher acute or late toxicities. Conclusion: SABR for larger lung tumours ≥5 cm results in high local control and acceptable survival in patients with medically inoperable large non-small cell lung carcinoma treated with radiation alone. Such patients should be considered for SABR owing to fewer treatment fractions and acceptable toxicity. Local control analysis reveals a sustained pattern of local failure emphasising the need for long-term follow-up. Improvements in technical strategies are required to further improve local control. Highlights: Stereotactic Ablative Radiation Therapy is safe and technically feasible for medically inoperable lung cancers larger than 5 cm. Large lung cancers have lower rates of local control and high rates of regional and distant failure. Toxicity of stereotactic ablative radiation therapy for larger lung tumours is acceptable.